Seasonal and daily upstream movements of brown trout Salmo trutta in an Iberian regulated river - García-Vega Ana; Sanz-Ronda Francisco Javier; Fuentes-Pérez Juan Francisco (Knowledge and Management of Aquatic Ecosystems, 2017)
Migrating fish are vulnerable to anthropogenic disturbances and, to assess the impact of human activities in freshwater ecosystems, it is vital to understand their movement patterns. The aim of this study is to describe the upstream movements of potamodromous brown trout Salmo trutta (seasonal and daily) and the potential environmental triggers in a regulated river in the northwest of the Iberian Peninsula (Porma River, León, Spain). Data collected in a fishway from October 2011 to January 2013 with a fish counter showed two important migratory periods, one associated with reproduction (October–December) and another one during summer (July–August). Both were significantly correlated with changes in solar radiation, flow and water temperature. Although in all seasons movements were identified throughout the day, they were more frequent early in the morning and in the afternoon during the spawning migration and in the morning during summer. River regulation of the Porma Reservoir significantly influenced movements by providing non-natural high flows during summer, which increased the chance of migration, but also colder water that could delay the thermoregulatory movements. In contrast, it provided lower flows in the spawning season. This highlights how susceptible brown trout movements are to human influence on flow and thermal regimes.